The synthesis and antistaphylococcal activity of dehydroabietic acid derivatives: Modifications at C-12. Issue 22 (15th November 2016) - Liu, Ming-Liang; Pan, Xue-Ying; Yang, Teng; Zhang, Wen-Ming; Wang, Tian-Qi; Wang, He-Yun; Lin, Hai-Xia; Yang, Cai-Guang; Cui, Yong-Mei
Graphical abstract: A series of 12-oxime and O -oxime ether derivatives of dehydroabietic acid were synthesized and evaluated for antistaphylococcal activities in S. aureus Newman and five multidrug-resistant strains. Abstract: A series of 12-oxime and O -oxime ether derivatives of dehydroabietic acid were synthesized and investigated for the antibacterial activity against Staphylococcus aureus Newman strain and five multidrug-resistant strains (NRS-1, NRS-70, NRS-100, NRS-108, and NRS-271). The aromatic oximate derivative11a showed the highest activity with MIC of 0.39–0.78 μg/mL against S. aureus Newman. Of note, compounds10b, 11 and14 showed the most potent antibacterial activity against five multidrug-resistant S. aureus with MIC values of 1.25–3.13 μg/mL. These results offered useful information for further strategic optimization in search of the antibacterial candidates against infection of multidrug-resistant Gram-positive bacteria.